Analisis Perbandingan Kualitas Layanan Sistem Antara Protokol HTTP dan MQTT Pada Monitoring Kelembaban Tanah - Anang Dwi Prakoso; Fikra Titan Syifa; Danny Kurnianto (PROtek : Jurnal Ilmiah Teknik Elektro, 2020)
This paper discusses the comparison of service quality between HTTP protocol and MQTT protocol implemented using internet of things to research on soil moisture around plants, quality of service compared to delay, jitter, throughput and packet loss. In this study the results showed that the HTTP and MQTT protocols have an average delay value below 150 or 63 ms. HTTP has an average jitter value between 0 - 62 ms, while MQTT has a jitter range value of between 0 - 16 ms. Whereas the HTTP throughput value is 88 ms and the MQTT protocol is 68 ms. Then for packet loss parameters both have the same quality as it generates a packet loss value of 0%. In this study it can be concluded that the use of http protocols is the superior protocol of MQTT in terms of quality of service.